2006
DOI: 10.1007/s11126-006-9007-x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Psychiatric Comorbidity on General Hospital Length of Stay

Abstract: Medical inpatients often suffer from comorbid psychiatric illness, which has been shown in previous studies to be associated with longer hospital stays. The present analysis used a large representative dataset to examine the impact of patient demographic and clinical characteristics on the relationship between psychiatric comorbidity and hospital length of stay. Analyses showed the existence of a psychiatric comorbidity predicted longer hospital stays for medical inpatients. However, in comparison to previous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 14 publications
3
45
0
2
Order By: Relevance
“…Patients with MHC spent more of FY03 on inpatient status than did patients with no MHC; this was a consistent and robust finding across every algorithm examined. This finding is consistent with other studies that have shown heavier use of inpatient services by patients with MHC [6,[14][15][16][17][18][19]. Our study also shows that some types of care (e.g., EXT) are associated with a disproportionately greater MHC effect.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Patients with MHC spent more of FY03 on inpatient status than did patients with no MHC; this was a consistent and robust finding across every algorithm examined. This finding is consistent with other studies that have shown heavier use of inpatient services by patients with MHC [6,[14][15][16][17][18][19]. Our study also shows that some types of care (e.g., EXT) are associated with a disproportionately greater MHC effect.…”
Section: Discussionsupporting
confidence: 93%
“…Prior studies both within and outside the VHA have documented that, compared with patients without MHCs, patients with MHCs tend to use more inpatient care [6,[14][15][16][17][18][19]. Thus, patients with MHCs represent a particularly high-intensity, high-cost group likely to merit special attention by VHA policy makers.…”
Section: Introductionmentioning
confidence: 99%
“…Depression is associated with longer medical hospital stays, particularly for older adults (Bressi, Marcus, & Solomon, 2006). Depressive symptoms are also associated with increased emergency department use for suicide-related injuries (Carter & Reymann, 2014), disproportionate hospital admissions (Nagamine, Jiang, & Merrill, 2006), and an increased likelihood of rehabilitation needs and inpatient death (Cullum, Metcalfe, Todd, & Brayne, 2008).…”
mentioning
confidence: 99%
“…Co-morbid psychiatric disorders and new onset of psychiatric disorders are associated with prolonged length of hospitalization [21]. Depressive symptoms may become manifest in older adults when recovery slows or functional abilities deteriorate.…”
Section: Literature Backgroundmentioning
confidence: 99%
“…A responsive system has in place a structured classification of mobility rating [12] that focuses on high risk older adults (i.e. women, those with limited education, multiple co-morbidities, pain and fatigue) who are less likely to walk independently while in hospital [2,14,21,29], and develop innovative programs to enhance the mobility of older adults, such as the "Walking for Wellness Program" [9].…”
Section: Responsive Proffesional Nurses Within a Responsive Systemmentioning
confidence: 99%